Incentive travellers’ proclivity to revisit an incentive destination. - M Potgieter; M Jacobs; S Geldenhuys (African Journal of Hospitality, Tourism and Leisure, 2016)
Incentive travel is a renowned motivator in talent management, and a gigantic victor for many tourism destinations. Destination marketing endeavours to leave a tourist with a positive and lasting impression, together with memorable experiences. Hoping that this will result in a return visit, recognised as more cost-effective than pursuing trial markets. However, the intricate nature of different constituents, and the strength of its influence involved, make incentive travel destination decision-making a complex process. Critical to destination marketers is knowledge concerning what constitutes a destination experience and the influence of this on specifically incentive travellers’ proclivity to revisit an incentive destination. The focus of this paper is on incentive travellers and their proclivity of returning to an incentive destination at a later stage, at their own time and expense. A deeper understanding of the most and least likely constituents influencing incentive travellers’ decision-making in this regard is required. A qualitative study with focus groups were undertaken to extract the expertise and experience of incentive travellers to facilitate insight and understanding of the complexities (feelings, thoughts and emotions) involved in the destination decision-making process. Deduced from the data obtained is that there are eight most likely (with accommodation as number one) and three least likely (health, personality and self-concept, and reference groups) constituents influencing the proclivity of returning to a destination visited as an incentive traveller. It is thus imperative for incentive destination planners and destination marketers to take cognisance of this when formulating their integrated marketing communication strategies to cultivate loyalty and the intention to return to a previously visited destination.